Attentional foci in modeling - Zentgraf, K. (dissertation.de, 2006)
Recent studies in motor learning suggest that directing attention to body parts can be disadvantageous for learning with respect to outcome variables compared to adopting an external focus, especially attending to the effects of one`s movements (Wulf & Prinz, 2001). However, few studies have investigated the phenomenon on the movement level.